Lenticel development and discolouration in the fruit of some mango (mangifera indica L.) cultivars - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2013)
Dissertation (MSc (Agric))--University of Pretoria, 2007.